Identification and characterization of pathogenic Pestalotiopsis species to pecan tree in Brazil - Marília Lazarotto; Marciéli Pitorini Bovolini; Marlove Fátima Brião Muniz; Ricardo Harakawa; Lia Rejane Silveira Reiniger; Álvaro Figueredo dos Santos (Pesquisa Agropecuária Brasileira, 2014)
The objective of this work was to characterize and cluster isolates of Pestalotiopsis species and to identify those that are pathogenic to pecan, based on morphological and molecular characters. Pestalotiopsis spp. isolates were identified by sequencing the internal transcribed spacer (ITS) and β?tubulin regions. Identification methods were compared to indicate the key morphological characters for species characterization. Thirteen isolates were used for the pathogenicity tests. Morphological characterization was performed using the following variables: mycelial growth rate, sporulation, colony pigmentation, and conidial length and width. Ten pathogenic isolates were identified, three as -tubulin regions. Identification methods were compared to indicate the key morphological characters for species characterization. Thirteen isolates were used for the pathogenicity tests. Morphological characterization was performed using the following variables: mycelial growth rate, sporulation, colony pigmentation, and conidial length and width. Ten pathogenic isolates were identified, three as Pestalotiopsis clavispora and three as P. cocculi. The other isolates remained as an undefined species. The morphological characters were efficient for an initial separation of the isolates, which were grouped according to differences at species level, mainly colony diameter, which was identified as an important morphological describer. Beta-tubulin gene sequencing was less informative than the ITS region sequencing for species identification.